Update to Practice Standards for Electrocardiographic Monitoring in Hospital Settings: A Scientific Statement From the American Heart Association. Issue 19 (7th November 2017) - Sandau, Kristin E.; Funk, Marjorie; Auerbach, Andrew; Barsness, Gregory W.; Blum, Kay; Cvach, Maria; Lampert, Rachel; May, Jeanine L.; McDaniel, George M.; Perez, Marco V.; Sendelbach, Sue; Sommargren, Claire E.; et al.
Abstract : Background and Purpose: This scientific statement provides an interprofessional, comprehensive review of evidence and recommendations for indications, duration, and implementation of continuous electro cardiographic monitoring of hospitalized patients. Since the original practice standards were published in 2004, new issues have emerged that need to be addressed: overuse of arrhythmia monitoring among a variety of patient populations, appropriate use of ischemia and QT-interval monitoring among select populations, alarm management, and documentation in electronic health records. Methods: Authors were commissioned by the American Heart Association and included experts from general cardiology, electrophysiology (adult and pediatric), and interventional cardiology, as well as a hospitalist and experts in alarm management. Strict adherence to the American Heart Association conflict of interest policy was maintained throughout the consensus process. Authors were assigned topics relevant to their areas of expertise, reviewed the literature with an emphasis on publications since the prior practice standards, and drafted recommendations on indications and duration for electrocardiographic monitoring in accordance with the American Heart Association Level of Evidence grading algorithm that was in place at the time of commissioning. Results: The comprehensive document is grouped into 5 sections: (1) Overview of Arrhythmia, Ischemia, and QTc Monitoring; (2) Recommendations for Indication and Duration of Electrocardiographic Monitoring presented by patient population; (3) Organizational Aspects: Alarm Management, Education of Staff, and Documentation; (4) Implementation of Practice Standards; and (5) Call for Research. Conclusions: Many of the recommendations are based on limited data, so authors conclude with specific questions for further research.